LncRNA LINC00944 Promotes Tumorigenesis but Suppresses Akt Phosphorylation in Renal Cell Carcinoma - Chen, Chiheng; Zheng, Hanxiong (Frontiers in Molecular Biosciences, 2021)
Long non-coding RNA (lncRNA) is a kind of RNA which possess longer than 200 nucleotides and lack of protein coding function. It was recognized as junk sequence for a long time. Recent studies have found that lncRNAs were actively function in almost every aspect of cell biology, and involved in a variety of biological functions. LncRNAs were closely related to a variety of human diseases, especially tumors. Recently, lncRNAs were being increasingly reported in renal cancer. In our study, we identified the expression of lncRNA LINC00944 was significantly elevated in RCC tissues and cell lines, high LINC00944 expression was significantly correlated with the tumor stage and prognosis of RCC. Knockdown of LINC00944 by CRISPR/dCas9-KRAB in higher-expressing 786-O and 769-P RCC cells could significantly decrease proliferation and migration, and also promote phosphorylation of Akt compared with control group. Our study is the first to report function of lncRNA LINC00944 in RCC. And we provide clinicopathological and experimental evidence that lncRNA LINC00944 acts as an oncogene in RCC which suggesting that targeting lncRNA LINC00944 expression might be a promising therapeutic strategy for the treatment of RCC.